The Post-Pandemic Reflection on Students’ Speaking Anxiety: A Case in Higher Education - Febria, Desty; Marsevani, Maya (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2024)
This research aims to find out students' perspectives and reflection regarding speaking skills in higher education. This research was conducted by involving 33 students from the batch of 2020 and 2021 in one of private universities in Batam. A case study design was employed by applying questionnaires and semi-structured interviews to collect the data. This research found that there were three categories which were the factors contributing to students' speaking anxiety in post-pandemic era. Those factors were communication apprehension, fear of negative evaluation, and test anxiety. In addition, to overcome their speaking anxiety, they used the methods of self-communication, self-healing, restarting the speech, and switching the language, while also learning and practicing in their effort to overcome their speaking anxiety. It is crucial to note that environment is also one of factors that affects students’ motivation in speaking skills. Hence, the lecturers hopefully can choose appropriate strategies to enhance students’ speaking skills, manage classroom environment well, and give positive reinforcement to students.